What is the product of (n - 8)(n + 2)?

Question

Asked 11/11/2014 12:12:27 PM

Updated 11/11/2014 1:15:51 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by andrewpallarca [11/11/2014 1:15:00 PM]

s

= 25/3 - 11/6;

= 50/6 - 11/6;

= 39/6;

= 13/2;

= 6 1/2

Question

Asked 11/11/2014 12:12:27 PM

Updated 11/11/2014 1:15:51 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by andrewpallarca [11/11/2014 1:15:00 PM]

Rating

8

(n - 8)(n + 2)

= n^2 + 2n - 8n - 16

= n^2 - 6n - 16

= n^2 + 2n - 8n - 16

= n^2 - 6n - 16

Added 11/11/2014 1:15:51 PM

This answer has been confirmed as correct and helpful.

Multiply (6z2 - 4z + 1)(8 - 3z).

Question

Not Answered

Updated 11/11/2014 12:22:20 PM

1 Answer/Comment

(6z2 - 4z + 1)(8 - 3z)

= 48z^2 - 18z^3 - 32z + 12z^2 + 8 - 3z

= - 18z^3 + 60z^2- 35z + 8

= 48z^2 - 18z^3 - 32z + 12z^2 + 8 - 3z

= - 18z^3 + 60z^2- 35z + 8

Added 11/11/2014 12:22:20 PM

This answer has been confirmed as correct and helpful.

Identify the polynomial.
x3y3

Question

Updated 11/12/2014 1:10:29 PM

1 Answer/Comment

x^3y^3 is a monomial.

Added 11/12/2014 1:10:29 PM

This answer has been confirmed as correct and helpful.

Write 6,000,370 in scientific notation. **Weegy:** 6,000,370 written in scientific notation is 6.00037 x 10^6 **User:** Find the seventh term of the following sequence?
1, 2, 4, ... (More)

Question

Not Answered

Updated 11/17/2014 7:07:22 AM

1 Answer/Comment

The seventh term of the following sequence: 1, 2, 4, is 64.

common ratio = 4/2 = 2

seventh term = 1*2^(7 - 1) = 2^6 = 64

common ratio = 4/2 = 2

seventh term = 1*2^(7 - 1) = 2^6 = 64

Added 11/16/2014 11:46:08 PM

This answer has been confirmed as correct and helpful.

Take 4a - 3b + 2c from 2a - 3b + 4c.

Question

Not Answered

Updated 12/4/2014 10:22:32 PM

1 Answer/Comment

Simplify.
(-2)^-3 **Weegy:** (-2)^-3 = 1/(-2)^3 = 1/(-8) = -1/8 **User:** Simplify.
y^-3 **User:** Simplify.
6x^-2 into fraction form (More)

Question

Not Answered

Updated 11/14/2014 3:18:43 PM

2 Answers/Comments

y^-3 = 1/y^3

Added 11/14/2014 3:18:12 PM

This answer has been confirmed as correct and helpful.

6x^-2 = 6/x^2

Added 11/14/2014 3:18:43 PM

This answer has been confirmed as correct and helpful.

34,466,974

questions answered

S

L

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

P

1

L

P

1

Points 818 [Total 6691] Ratings 19 Comments 628 Invitations 0 Offline

There are no comments.